Study of the Human Microbiota Under Physiological Conditions (Molecular Medicine Communications, 2023)
Profiling the human intestinal environment under physiological conditions involves characterizing the various components and factors in the gut to understand its normal functioning. This profiling can encompass multiple aspects, including the microbiome, host immune response, metabolites, and the physical environment of the intestine. Shalon and colleagues developed an ingestible device that collects samples from multiple regions of the human intestinal tract during normal digestion. The collection of 240 intestinal samples from 15 healthy individuals using the device and subsequent multi-omics analyses identified significant differences between bacteria, phages, host proteins, and metabolites in the intestines versus stool. Certain microbial taxa were differentially enriched, and prophage induction was more prevalent in the intestines than in stool. The host proteome and bile acid profiles varied along the intestines and were highly distinct from those of stool. Correlations between gradients in bile acid concentrations and microbial abundance predicted species that altered the bile acid pool through deconjugation. Furthermore, microbially conjugated bile acid concentrations exhibited amino acid-dependent trends that were not apparent in the stool. Overall, non-invasive, longitudinal profiling of microorganisms, proteins, and bile acids along the intestinal tract under physiological conditions can help elucidate the roles of the gut microbiome and metabolome in human physiology and disease. Nature. 2023 May;617(7961):581-591.  doi: 10.1038/s41586-023-05989-7.